Electroless nickel plating and spontaneous infiltration behavior of woven carbon fibers. (15th January 2020) - Zhang, Junjia; Liu, Shichao; Liu, Jiaming; Lu, Yiping; Liu, Yue; Li, Tingju
Abstract: The effects of electroless Ni plating on the interaction between molten aluminium and carbon fibers was studied to investigate the fabrication of woven carbon fiber-reinforced Al-matrix composites by liquid processing. An appropriate electroless plating method for coating carbon fibers in woven form was developed. The uniform and compact coatings could be generated stably at a temperature of 70 °C and pH 4.0, and the addition of a disperser improved the deep plating ability and promoted bidirectional plating. More than 80% of the coated woven fibers exhibited excellent coating properties, which offered sufficient fixation and protection of the fibers for subsequent processing. A synchrotron X-ray radiography analysis indicated that the spontaneous infiltration behavior mainly stemmed from the chemical reaction between Al and Ni, rather than the simple physical filling of the fiber interspaces with molten aluminium. The infiltration process could be divided into three typical periods, namely the slow infiltration, rapid infiltration, and stable infiltration periods. Moreover, the coated fibers oriented in the direction perpendicular to the infiltration direction were more easily infiltrated than those oriented in the direction parallel to the infiltration direction. Graphical abstract: Image 1 Highlights: Electroless nickel plating technology was successfully optimized for woven carbon fibers, and more than 80% of the coated woven fibers exhibited excellent coating properties. A synchrotron X-ray radiography analysis revealed the spontaneous infiltration mechanism between the coated woven carbon fibers and the molten aluminium. The spontaneous infiltration mainly involved Al–Ni interdiffusion; the coated fibers oriented in the direction perpendicular to the infiltration direction were more easily infiltrated than the others. The main factors influencing the spontaneous infiltration behavior were studied systematically, and the infiltration process was divided into three periods.